Caspase-dependent degradation of MDMx/MDM4 cell cycle regulatory protein in amyloid β-induced neuronal damage. (16th November 2015) - Colacurcio, Daniel J.; Zyskind, Jacob W.; Jordan-Sciutto, Kelly L.; Espinoza, Cagla Akay
Highlights: Age-dependent reduction in MDMx levels in cholinergic neurons in Tg2576 murine model of AD. Caspase-dependent degradation of MDMx in neurons exposed to amyloid beta in vitro . Abstract: MDMx/MDM4 is a negative regulator of the p53 tumor suppressor protein and is necessary for survival in dividing cells. MDMx is also expressed in postmitotic neurons, with prosurvival roles that are independent of its extensively described roles in carcinogenesis. We and others have shown a role for MDMx loss in neuronal death in vitro and in vivo in several neurodegenerative diseases. Further, we have recently shown that MDMx is targeted for proteolytic degradation by calcium-dependent proteases, calpains, in neurons in vitro, and that MDMx overexpression provided partial neuroprotection in a model of HIV-associated neurodegeneration. Here, we assessed whether amyloid β (Aβ)-induced MDMx degradation occurred in Alzheimer's Disease (AD) models. Our data shows an age-dependent reduction in MDMx levels in cholinergic neurons within the cortex of adult mice expressing the swedish mutant of the amyloid precursor protein, APP in the Tg2576 murine model of AD. In vitro, Aβ treatment of primary cortical neurons led to the caspase-dependent MDMx degradation. Our findings suggest that MDMx degradation associated with neuronal death occurs via caspase activation in neurons, and that the progressive loss of MDMx protein represents a potential mechanism of Aβ-induced neuronal death during disease progression in AD.